The need to understand the stability of arctic vegetation during rapid climate change: An assessment of imbalance in the literature - Terry V. Callaghan; Roberto Cazzolla Gatti; Gareth Phoenix (Ambio, 2022)

Siberian environmental change: Synthesis of recent studies and opportunities for networking - Terry V. Callaghan; Olga Shaduyko; Sergey N. Kirpotin; Evgeny Gordov (Ambio, 2021)

The dynamic land-cover of the Altai Mountains: Perspectives based on past and current environmental and biodiversity changes - Igor V. Volkov; Valeriy A. Zemtsov; Alexander A. Erofeev; Andrey S. Babenko; Anastasia I. Volkova; Terry V. Callaghan (Ambio, 2021)

South-Siberian mountain mires: Perspectives on a potentially vulnerable remote source of biodiversity - Irina I. Volkova; Terry V. Callaghan; Igor V. Volkov; Natalia A. Chernova; Anastasia I. Volkova (Ambio, 2021)

Impacts of environmental change on biodiversity and vegetation dynamics in Siberia - Sergey N. Kirpotin; Terry V. Callaghan; Anna M. Peregon; Andrei S. Babenko; Daniil I. Berman; Nina A. Bulakhova; Arysia A. Byzaakay; Tatiana M. Chernykh; Vladislav Chursin; Elena A. Interesova; Sergey P. Gureev; Ivan A. Kerchev; et al. (Ambio, 2021)

The rise of the Arctic: Intergenerational personal perspectives - Terry V. Callaghan; Margareta Johansson (Ambio, 2021)

The missing pieces for better future predictions in subarctic ecosystems: A Torneträsk case study - Didac Pascual; Jonas Åkerman; Marina Becher; Terry V. Callaghan; Torben R. Christensen; Ellen Dorrepaal; Urban Emanuelsson; Reiner Giesler; Dan Hammarlund; Edward Hanna; Annika Hofgaard; Hongxiao Jin; et al. (Ambio, 2021)
Arctic and subarctic ecosystems are experiencing substantial changes in hydrology, vegetation, permafrost conditions, and carbon cycling, in response to climatic change and other anthropogenic drivers, and these changes are likely to continue over this century. The total magnitude of these changes results from multiple interactions among these drivers. Field measurements can address the overall responses to different changing drivers, but are less capable of quantifying the interactions among them. Currently, a comprehensive assessment of the drivers of ecosystem changes, and the magnitude of their direct and indirect impacts on subarctic ecosystems, is missing. The Torneträsk area, in the Swedish subarctic, has an unrivalled history of environmental observation over 100 years, and is one of the most studied sites in the Arctic. In this study, we summarize and rank the drivers of ecosystem change in the Torneträsk area, and propose research priorities identified, by expert assessment, to improve predictions of ecosystem changes. The research priorities identified include understanding impacts on ecosystems brought on by altered frequency and intensity of winter warming events, evapotranspiration rates, rainfall, duration of snow cover and lake-ice, changed soil moisture, and droughts. This case study can help us understand the ongoing ecosystem changes occurring in the Torneträsk area, and contribute to improve predictions of future ecosystem changes at a larger scale. This understanding will provide the basis for the future mitigation and adaptation plans needed in a changing climate.

Improving dialogue among researchers, local and indigenous peoples and decision-makers to address issues of climate change in the North - Terry V. Callaghan; Olga Kulikova; Lidia Rakhmanova; Elmer Topp-Jørgensen; Niklas Labba; Lars-Anders Kuhmanen; Sergey Kirpotin; Olga Shaduyko; Henry Burgess; Arja Rautio; Ruth S. Hindshaw; Leonid L. Golubyatnikov; et al. (Ambio, 2020)
The Circumpolar North has been changing rapidly within the last decades, and the socioeconomic systems of the Eurasian Arctic and Siberia in particular have displayed the most dramatic changes. Here, anthropogenic drivers of environmental change such as migration and industrialization are added to climate-induced changes in the natural environment such as permafrost thawing and increased frequency of extreme events. Understanding and adapting to both types of changes are important to local and indigenous peoples in the Arctic and for the wider global community due to transboundary connectivity. As local and indigenous peoples, decision-makers and scientists perceive changes and impacts differently and often fail to communicate efficiently to respond to changes adequately, we convened a meeting of the three groups in Salekhard in 2017. The outcomes of the meeting include perceptions of how the three groups each perceive the main issues affecting health and well-being and recommendations for working together better.

Changing Arctic snow cover: A review of recent developments and assessment of future needs for observations, modelling, and impacts - Stef Bokhorst; Stine Højlund Pedersen; Ludovic Brucker; Oleg Anisimov; Jarle W. Bjerke; Ross D. Brown; Dorothee Ehrich; Richard L. H. Essery; Achim Heilig; Susanne Ingvander; Cecilia Johansson; Margareta Johansson; et al. (Ambio, 2016)

Tight Coupling Between Shoot Level Foliar N and P, Leaf Area, and Shoot Growth in Arctic Dwarf Shrubs Under Simulated Climate Change - Eva K. Koller; Malcolm C. Press; Terry V. Callaghan; Gareth K. Phoenix (Ecosystems, 2016)

Climatic and biotic extreme events moderate long‐term responses of above‐ and belowground sub‐Arctic heathland communities to climate change - Stef Bokhorst; Gareth K. Phoenix; Matty P. Berg; Terry V. Callaghan; Christopher Kirby‐Lambert; Jarle W. Bjerke (Global Change Biology, 2015)
Climate change impacts are not uniform across the Arctic region because interacting factors causes large variations in local ecosystem change. Extreme climatic events and population cycles of herbivores occur simultaneously against a background of gradual climate warming trends and can redirect ecosystem change along routes that are difficult to predict. Here, we present the results from sub‐Arctic heath vegetation and its belowground micro‐arthropod community in response to the two main drivers of vegetation damage in this region: extreme winter warming events and subsequent outbreaks of the defoliating autumnal moth caterpillar ( Epirrita autumnata ). Evergreen dwarf shrub biomass decreased (30%) following extreme winter warming events and again by moth caterpillar grazing. Deciduous shrubs that were previously exposed to an extreme winter warming event were not affected by the moth caterpillar grazing, while those that were not exposed to warming events (control plots) showed reduced (23%) biomass from grazing. Cryptogam cover increased irrespective of grazing or winter warming events. Micro‐arthropods declined (46%) following winter warming but did not respond to changes in plant community. Extreme winter warming and caterpillar grazing suppressed the CO 2 fluxes of the ecosystem. Evergreen dwarf shrubs are disadvantaged in a future sub‐Arctic with more stochastic climatic and biotic events. Given that summer warming may further benefit deciduous over evergreen shrubs, event and trend climate change may both act against evergreen shrubs and the ecosystem functions they provide. This is of particular concern given that Arctic heath vegetation is typically dominated by evergreen shrubs. Other components of the vegetation showed variable responses to abiotic and biotic events, and their interaction indicates that sub‐Arctic vegetation response to multiple pressures is not easy to predict from single‐factor responses. Therefore, while biotic and climatic events may have clear impacts, more work is needed to understand their net effect on Arctic ecosystems.

Future vegetation changes in thawing subarctic mires and implications for greenhouse gas exchange—a regional assessment - Julia Bosiö; Margareta Johansson; Terry V. Callaghan; Bernt Johansen; Torben R. Christensen (Climatic Change, 2012)

Changes Versus Homeostasis in Alpine and Sub-Alpine Vegetation Over Three Decades in the Sub-Arctic - Henrik Hedenås; Bengt Å. Carlsson; Urban Emanuelsson; Alistair D. Headley; Christer Jonasson; Brita M. Svensson; Terry V. Callaghan (Ambio, 2012)

Enhanced UV-B and Elevated CO2 Impacts Sub-Arctic Shrub Berry Abundance, Quality and Seed Germination - Dylan Gwynn-Jones; Alan G. Jones; Alice Waterhouse; Ana Winters; David Comont; John Scullion; Rosie Gardias; Bente J. Graee; John A. Lee; Terry V. Callaghan (Ambio, 2012)

Linking Fine-Scale Sub-Arctic Vegetation Distribution in Complex Topography with Surface-Air-Temperature Modelled at 50-m Resolution - Zhenlin Yang; Martin T. Sykes; Edward Hanna; Terry V. Callaghan (Ambio, 2012)

Environmental Monitoring and Research in the Abisko Area—An Overview - Christer Jonasson; Mats Sonesson; Torben R. Christensen; Terry V. Callaghan (Ambio, 2012)

Arctic warming on two continents has consistent negative effects on lichen diversity and mixed effects on bryophyte diversity - Simone I. Lang; Johannes H. C. Cornelissen; Gaius R. Shaver; Matthias Ahrens; Terry V. Callaghan; Ulf Molau; Cajo J. F. Ter Braak; Adam Hölzer; Rien Aerts (Global Change Biology, 2012)
Little is known about the impact of changing temperature regimes on composition and diversity of cryptogam communities in the A rctic and S ubarctic, despite the well‐known importance of lichens and bryophytes to the functioning and climate feedbacks of northern ecosystems. We investigated changes in diversity and abundance of lichens and bryophytes within long‐term (9–16 years) warming experiments and along natural climatic gradients, ranging from S wedish subarctic birch forest and subarctic/subalpine tundra to A laskan arctic tussock tundra. In both S weden and A laska, lichen diversity responded negatively to experimental warming (with the exception of a birch forest) and to higher temperatures along climatic gradients. Bryophytes were less sensitive to experimental warming than lichens, but depending on the length of the gradient, bryophyte diversity decreased both with increasing temperatures and at extremely low temperatures. Among bryophytes, S phagnum mosses were particularly resistant to experimental warming in terms of both abundance and diversity. Temperature, on both continents, was the main driver of species composition within experiments and along gradients, with the exception of the S wedish subarctic birch forest where amount of litter constituted the best explanatory variable. In a warming experiment in moist acidic tussock tundra in A laska, temperature together with soil ammonium availability were the most important factors influencing species composition. Overall, dwarf shrub abundance (deciduous and evergreen) was positively related to warming but so were the bryophytes S phagnum girgensohnii , H ylocomium splendens and P leurozium schreberi ; the majority of other cryptogams showed a negative relationship to warming. This unique combination of intercontinental comparison, natural gradient studies and experimental studies shows that cryptogam diversity and abundance, especially within lichens, is likely to decrease under arctic climate warming. Given the many ecosystem processes affected by cryptogams in high latitudes (e.g. carbon sequestration, N 2 ‐fixation, trophic interactions), these changes will have important feedback consequences for ecosystem functions and climate.

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Feedbacks and Interactions: From the Arctic Cryosphere to the Climate System - Terry V. Callaghan; Margareta Johansson; Jeff Key; Terry Prowse; Maria Ananicheva; Alexander Klepikov (Ambio, 2011)

Multiple Effects of Changes in Arctic Snow Cover - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Raymond S. Bradley; Sylvie Blangy; Olga N. Bulygina; Torben R. Christensen; Jonathan E. Colman; Richard L. H. Essery; et al. (Ambio, 2011)

Ecological Implications of Changes in the Arctic Cryosphere - Warwick F. Vincent; Terry V. Callaghan; Dorthe Dahl-Jensen; Margareta Johansson; Kit M. Kovacs; Christine Michel; Terry Prowse; James D. Reist; Martin Sharp (Ambio, 2011)

The Changing Face of Arctic Snow Cover: A Synthesis of Observed and Projected Changes - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Roger G. Barry; Olga N. Bulygina; Richard L. H. Essery; D. M. Frolov; Vladimir N. Golubev; Thomas C. Grenfell; et al. (Ambio, 2011)

Preface - Morten Skovgaard Olsen; Lars-Otto Reiersen; Terry V. Callaghan; Terry Prowse; Margareta Johansson (Ambio, 2011)

Multi-Decadal Changes in Snow Characteristics in Sub-Arctic Sweden - Cecilia Johansson; Veijo A. Pohjola; Christer Jonasson; Terry V. Callaghan (Ambio, 2011)

Past and Present Permafrost Temperatures in the Abisko Area: Redrilling of Boreholes - Margareta Johansson; Jonas Åkerman; Frida Keuper; Torben R. Christensen; Hugues Lantuit; Terry V. Callaghan (Ambio, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Tree and Shrub Expansion Over the Past 34 Years at the Tree-Line Near Abisko, Sweden - Sara Rundqvist; Henrik Hedenås; Anneli Sandström; Urban Emanuelsson; Håkan Eriksson; Christer Jonasson; Terry V. Callaghan (Ambio, 2011)

Changes in Tree Growth, Biomass and Vegetation Over a 13-Year Period in the Swedish Sub-Arctic - Henrik Hedenås; Håkan Olsson; Christer Jonasson; Johan Bergstedt; Ulrika Dahlberg; Terry V. Callaghan (Ambio, 2011)

Plant and Vegetation Dynamics on Disko Island, West Greenland: Snapshots Separated by Over 40 Years - Terry V. Callaghan; Torben R. Christensen; Elin J. Jantze (Ambio, 2011)

Multi-decadal Changes in Tundra Environments and Ecosystems: The International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Patrick J. Webber (Ambio, 2011)

Plant species traits are the predominant control on litter decomposition rates within biomes worldwide - William K. Cornwell; Johannes H. C. Cornelissen; Kathryn Amatangelo; Ellen Dorrepaal; Valerie T. Eviner; Oscar Godoy; Sarah E. Hobbie; Bart Hoorens; Hiroko Kurokawa; Natalia Pérez‐Harguindeguy; Helen M. Quested; Louis S. Santiago; et al. (Ecology Letters, 2008)
Worldwide decomposition rates depend both on climate and the legacy of plant functional traits as litter quality. To quantify the degree to which functional differentiation among species affects their litter decomposition rates, we brought together leaf trait and litter mass loss data for 818 species from 66 decomposition experiments on six continents. We show that: (i) the magnitude of species‐driven differences is much larger than previously thought and greater than climate‐driven variation; (ii) the decomposability of a species’ litter is consistently correlated with that species’ ecological strategy within different ecosystems globally, representing a new connection between whole plant carbon strategy and biogeochemical cycling. This connection between plant strategies and decomposability is crucial for both understanding vegetation–soil feedbacks, and for improving forecasts of the global carbon cycle.

Future changes in vegetation and ecosystem function of the Barents Region - Annett Wolf; Terry V. Callaghan; Karin Larson (Climatic Change, 2008)

Impact of non-outbreak insect damage on vegetation in northern Europe will be greater than expected during a changing climate - Annett Wolf; Mikhail V. Kozlov; Terry V. Callaghan (Climatic Change, 2008)

Global negative vegetation feedback to climate warming responses of leaf litter decomposition rates in cold biomes - Johannes H.C. Cornelissen; Peter M. Van Bodegom; Rien Aerts; Terry V. Callaghan; Richard S.P. Van Logtestijn; Juha Alatalo; F. Stuart Chapin; Renato Gerdol; Jon Gudmundsson; Dylan Gwynn‐Jones; Anne E. Hartley; David S. Hik; et al. (Ecology Letters, 2007)
Whether climate change will turn cold biomes from large long‐term carbon sinks into sources is hotly debated because of the great potential for ecosystem‐mediated feedbacks to global climate. Critical are the direction, magnitude and generality of climate responses of plant litter decomposition. Here, we present the first quantitative analysis of the major climate‐change‐related drivers of litter decomposition rates in cold northern biomes worldwide. Leaf litters collected from the predominant species in 33 global change manipulation experiments in circum‐arctic‐alpine ecosystems were incubated simultaneously in two contrasting arctic life zones. We demonstrate that longer‐term, large‐scale changes to leaf litter decomposition will be driven primarily by both direct warming effects and concomitant shifts in plant growth form composition, with a much smaller role for changes in litter quality within species. Specifically, the ongoing warming‐induced expansion of shrubs with recalcitrant leaf litter across cold biomes would constitute a negative feedback to global warming. Depending on the strength of other (previously reported) positive feedbacks of shrub expansion on soil carbon turnover, this may partly counteract direct warming enhancement of litter decomposition.

Effects of elevated solar UV-B radiation from ozone depletion on terrestrial ecosystems - Qing Liu; Terry V. Callaghan; Yuanyuan Zuo (Journal of Mountain Science, 2004)

Summer warming and increased winter snow cover affect Sphagnum fuscum growth, structure and production in a sub‐arctic bog - Ellen Dorrepaal; Rien Aerts; Johannes H. C. Cornelissen; Terry V. Callaghan; Richard S. P. Van Logtestijn (Global Change Biology, 2004)
Sphagnum mosses form a major component of northern peatlands, which are expected to experience substantially higher increases in temperature and winter precipitation than the global average. Sphagnum may play an important role in the responses of the global carbon cycle to climate change. We investigated the responses of summer length growth, carpet structure and production in Sphagnum fuscum to experimentally induced changes in climate in a sub‐arctic bog. Thereto, we used open‐top chambers (OTCs) to create six climate scenarios including changes in summer temperatures, and changes in winter snow cover and spring temperatures. In winter, the OTCs doubled the snow thickness, resulting in 0.5–2.8°C higher average air temperatures. Spring air temperatures in OTCs increased by 1.0°C. Summer warming had a maximum effect of 0.9°C, while vapor pressure deficit was not affected. The climate manipulations had strong effects on S. fuscum . Summer warming enhanced the length increment by 42–62%, whereas bulk density decreased. This resulted in a trend ( P Sphagnum structure on moisture holding and transporting capacity. Moreover, the strong length growth enhancement may affect interactions with other mosses and vascular plants. Because winter snow addition enhanced the production of S. fuscum without affecting its structure, it may increase the carbon balance of northern peatlands.

Litter of the hemiparasite Bartsia alpina enhances plant growth: evidence for a functional role in nutrient cycling - Helen M. Quested; Malcolm C. Press; Terry V. Callaghan (Oecologia, 2003)

Ecological importance of ambient solar ultraviolet radiation to a sub-arctic heath community - Gareth K. Phoenix; Dylan Gwynn-Jones; John A. Lee; Terry V. Callaghan (Plant Ecology, 2003)

The nitrogen fixation potential of arctic cryptogram species is influenced by enhanced UV-B radiation - Bjørn Solheim; Ulf Johanson; Terry V. Callaghan; John A. Lee; Dylan Gwynn-Jones; Lars O. Björn (Oecologia, 2002)

The hemiparasitic angiosperm Bartsia alpina has the potential to accelerate decomposition in sub-arctic communities - Helen M. Quested; Malcolm C. Press; Terry V. Callaghan; Hans J. Cornelissen (Oecologia, 2002)

The direct effects of UV-B radiation on Betula pubescens litter decomposing at four European field sites - Sandra A. Moody; Nigel D. Paul; Lars Olof Björn; Terry V. Callaghan; John A. Lee; Yiannis Manetas; Jelte Rozema; Dylan Gwynn-Jones; Ulf Johanson; Aris Kyparissis; Annemiek M.C. Oudejans (Plant Ecology, 2001)